The virtues of small grain size: Potential pathways to a distinguishing feature of Asian wheats. (28th December 2016) - Liu, Xinyi; Lister, Diane L.; Zhao, Zhijun; Staff, Richard A.; Jones, Penelope J.; Zhou, Liping; Pokharia, Anil K.; Petrie, Cameron A.; Pathak, Anubha; Lu, Hongliang; Matuzeviciute, Giedre Motuzaite; Bates, Jennifer; et al.
Abstract: Increase in grain/seed size recurrently features as a key element in the 'domestication syndrome' of plants ( cf . Zohary and Hopf 2000; Fuller et al. 2014). In the context of its spread across Eurasia, however, the grain size of one of the world's major crop species underwent a substantial reduction. Between the fifth and second millennia BC, the grain length in a number of species of Triticum, collectively known as free-threshing wheat, decreased by around 30%. In order to understand and help account for this trend, we have obtained direct radiocarbon measurements from 51 charred wheat grains and measured the dimensions of several hundred grains from Asia to establish when and where that size diminution occurred. Our results indicate that the pace of a eastward/southward spread was interrupted around 1800 BC on the borders of the distinct culinary zone recognized by Fuller and Rowlands (2011), but regained pace around 200–300 years later in central-east China with a diminished grain size. We interpret this as evidence of a period of active crop selection to suit culinary needs, and consider whether it constitutes a distinct episode in the general character of genetic intervention in domesticated species.